Anomaly Detection on ATMs via Time Series Motif Discovery - Deppe, Sahar; Dicks, Alexander; Lohweg, Volker (21th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA 2016), Berlin,)
Cash machines or automated teller machines (ATMs) are one of the typical ways to get cash around the world. Such machines are under a variety of criminal attacks. Most of the manipulations are performed through skimming. In 2014, such attacks led to a damage of approx. 280 million Euro within the EU. In this paper, we propose an approach to detect anomalies and attacks on ATMs via motif discovery. Motifs are frequently unknown occurring sequences or events in a time series signal. State of the ATM is captured by innovative piezoelectric sensor networks to analyse the occurring vibrations. The captured signals are inspected by the Complex Quad-Tree Wavelet Packet transform which provides broad frequency analysis of a signal in various scales. Next, features are extracted from the selected scale based on the information content, to detect motifs. Detected motifs provide the prototype patterns for anomaly detection or classification tasks.